TEACHING READING FOR YOUNG STUDENTS: A CASE STUDY AT ELEMENTARY STUDENTS IN CIPUTAT, SOUTH TANGERANG - Ummi Kultsum; Ratna Sari Dewi; Nadrah Nadrah (Journal of Early Childhood Education (JECE), 2021)
The objective of this study is to find that reading a story is more effective to develop student’s reading comprehension. This research was held in an English course at IC Multi Ciputat with 20 children’s participants. The sample was divided into experiment groups consist of 10 participants and a control class with 10 participants. The experimental study conducted as a research design. The data collected from the pre-test and post-test of the two groups showed the mean of student’s achievement in experiment class was 72.8 on pre-test and 92.9 on post-test. Meanwhile, the mean score of students score in the control class was 73.6 on the pre-test and 87.6 on the post-test. These data indicated a small impact for children to develop their reading comprehension through a storybook.